2022
DOI: 10.1371/journal.pntd.0010988
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes, and practices regarding Crimean-Congo hemorrhagic fever among general people: A cross-sectional study in Pakistan

Abstract: Background Crimean-Congo hemorrhagic fever (CCHF) continues to pose a serious threat to the fragile healthcare system of Pakistan with a continuous increase of morbidity and mortality. The present study aimed to assess the knowledge, attitudes, and practices regarding CCHF among general people who resided in Pakistan. Methods An online cross-sectional survey design was applied, and a convenience sampling technique was used to recruit 1039 adult people from Pakistan. Data were collected from September 08 to O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Knowledge of the disease is considered the first steppingstone to any good measures such as health education activity that is implemented. Knowing the causes and transmission sources of a disease, increases the likelihood that people will become more aware of the spread of bat borne diseases, and of the preventive measures to slow transmission [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowledge of the disease is considered the first steppingstone to any good measures such as health education activity that is implemented. Knowing the causes and transmission sources of a disease, increases the likelihood that people will become more aware of the spread of bat borne diseases, and of the preventive measures to slow transmission [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Poor attitudes of people towards bats coupled with hunting of bats for food and medicinal purposes potentially exposes communities to infectious agents as well as threaten the long-term viability of local bat populations [ 14 ]. Understanding the level of knowledge and attitude of community towards bats is thus important to design effective community awareness campaigns aimed at preventing spillover [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the increasing claims for the potential health threat associated with CCHFV infection [ 5 , 6 ], this pathogen often remains underestimated, not only by the general population, but also among healthcare professionals [ 64 , 65 ]. Nonetheless, pooled data stress how CCHFV infection may represent a far more common occurrence, even in countries and settings not usually associated with CCHF.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to Jamil et al who found a lower overall good practice rate (48.2%) among participants in managing Crimean-Congo hemorrhagic fever. 14 In terms of antibiotic usage, the preference for ceftriaxon (67%) aligns with current treatment guidelines, yet the varied responses indicate a lack of consensus or potential overreliance on certain antibiotics, a concern also echoed in Boran and Kahriman's study on fever management. 15 The attitude and practice patterns revealed in the study, such as 61% always providing supportive care and 17.5% always applying empirical antibiotics, reflect a proactive approach towards management but also highlight the need for more standardized treatment protocols.…”
Section: Discussionmentioning
confidence: 99%